Pengaruh Lingkungan Kerja terhadap Kepuasan Kerja Pegawai pada Kantor Dinas Perumahan, Kawasan Permukiman dan Pertanahan Provinsi Sulawesi Selatan - Ady andardinata (Sekolah Tinggi Ilmu Ekonomi (STIE) Tri Dharma Nusantara Makassar, 2022)
The Effect of Work Environment on Job Satisfaction Employees at the Office of the Housing, Settlement and Land Office of South Sulawesi Province. This study aims to determine the effect of work environment on job satisfaction employees at the housing, residential and land office of South Sulawesi province . The types of data used in this research are qualitative and quantitative data. The data sources are obtained from primary and secondary data by distributing questions or statements to respondents. The number of respondents used is 54 people. The method used in processing the data is simple linear regression analysis, correlation coefficient, coefficient of determination and t test so that the research results show that the work environment has a positive and significant effect on employee performance.at the Office of the Housing, Settlement and Land Office of South Sulawesi Province